Advanced lung cancer classification approach adopting modified graph clustering and whale optimisation‐based feature selection technique accompanied by a hybrid ensemble classifier. Issue 10 (8th July 2020) - Mary Adline Priya, Michael; Joseph Jawhar, S.
Abstract : Nowadays, lung cancer is the leading cause of cancer death in both men and women. The early detection of potentially cancerous cells is the best way to improve the patient's chances of survival. In the medical field, computed tomography (CT) is the best imaging technique and it is helpful for doctors to accurately find the cancerous cells. The authors propose an automatic approach to analyse and segment the lungs and classify each lung into normal or cancer. Initially, the CT lung image is pre‐processed to remove noise. Then, they combine the histogram analysis with thresholding and morphological operations to segment and extract the lung regions. In feature extraction stage, the radiomic features of each lung image are extracted separately. Then to improve the classification accuracy, some of the optimum features are selected using modified graph clustering‐based whale optimisation algorithm. Finally, the selected features are classified using ensemble classifiers such as support vector machine, K‐nearest neighbour, and random forest. Experimental result demonstrates that the proposed method achieves better performance in terms of sensitivity, specificity, precision, recall, F ‐measure, and accuracy when compared with other state‐of‐art approaches.